Policing Farm Crime in the United States: A Research Note - Lynn, Brianna; Osborne, Dustin L.; Edwards, Bradley (International Journal of Rural Criminology, 2023)
Though research on farm-related offending and victimization still lags behind most other crime-related topics, recent years have seen an increase in scholarly attention to the topic. These studies have provided insight into the prevalence of victimization and the impact of various security measures on it. However, virtually all of these studies have relied upon data collected from farm operators. While beneficial, it is also imperative to explore the experiences and perceptions of those tasked with investigating these crimes. The current study sought to fill this gap in the literature through qualitative interviews with agricultural crime investigators in the United States. Specifically, interviewees were asked to elaborate on topics such as the referral of cases, how they are typically processed, and perceptions regarding the prevalence of victimization and characteristics of both victims and offenders. Themes emerging from their responses are discussed. In addition, both policy implications and potential directions for future research are highlighted.